Thoracoscopic ablation for symptomatic atrial fibrillation improves quality of life. (14th October 2021) - Vos, L.M; Vos, P.W.K; Nieuwkerk, P.T; Vos, R; Havenaar, H; Hofman, F.N; Boersma, L.V.A; Van Putte, B.P
Abstract: Background: Rhythm control has become an essential part of adequate management in atrial fibrillation (AF) to reduce symptoms and ultimately to improve health related quality of life (HRQoL). Totally thoracoscopic ablation has been established over the last years as an effective and safe rhythm control strategy, especially for persistent AF, but quality of life data are lacking. Purpose: To assess the impact of totally thoracoscopic ablation on HRQoL in patients with symptomatic AF. Methods: Consecutive patients with symptomatic AF undergoing totally thoracoscopic ablation at a referral centre in the Netherlands (July 2016 – October 2019) were included. The primary outcome was quality of life. Short Form 36 and Atrial Fibrillation Effect on Quality-of-Life (AFEQT) health surveys were collected at baseline, 1, 3, 6 and 12 months. Clinical improvement was measured as the relative increase of the QoL-score at 1 year compared to the baseline score (in %). Multilevel regression modelling was used, coupled with fractional polynomials for adjustment of age differences and nonlinear time trends, to investigate the one-year clinical trajectories of sex differences in QoL subscales. Secondary outcomes included rhythm success (freedom from any recurrence of atrial tachyarrhythmia>30 sec), mortality and stroke. Results: 191 patients were included (63.9±8.6 years, 68% male, 22.5% paroxysmal AF, 69.6% persistent AF and 7.9% long-term persistent AF, 66.5% having at least one previous failed catheter ablation, with median Cha2ds2 Vasc score of 2 [IQR 1–3]). AFEQT sum scores (52.6 points at baseline) substantially improved after three months (49.8%; p<0.001) and remained stable up to 1-year (54.2%; p<0.001) despite adverse events. Patients with recurrent AF also showed significant improvement at 3 months which remained stable up to 1-year, but patients who remained in sinus rhythm had significantly more increase (61.3% vs 26.9%, p<.001). The SF36 physical and mental summary composite scores significantly improved after 3 months (12.3% and 11.9% respectively; p<.001) and remained stable up to 1-year (16.9% and 16.4% respectively; P<.001). Although female patients had significantly lower AFEQT and physical subscales at baseline, similar improvement in scores were observed over time compared to men, adjusted for age and sex interactions (P<.001). One-year stroke rate was 1.6 per 100 patient-years with an oral anticoagulation rate of 63%. One-year survival was 99.5%. Conclusions: This study reveals significant improvement of HRQoL three months after thoracoscopic ablation that persisted up to 1-year, also when adjusted for sex and age differences. Despite AF recurrence or adverse events AF related QoL still improved. Trials are necessary to confirm these data. Funding Acknowledgement: Type of funding sources: None.